English for Business Communication - Chan, Mable (Routledge applied English language introductions, 2020)
This textbook provides a comprehensive introduction for students and professionals who are studying English for business or workplace communication and covers both spoken and written English. Based on up-to-date research in business communication and incorporating an international range of real-world authentic texts, this book deals with the realities of communication in business today.